Narratives of Mothers: An Optimistic View of Raising Children with Disabilities - Joshi, Priti (Indonesian Journal of Disability Studies, 2021)
The study explored the experiences of 49 mothers of children with disabilities through interviews at home. The children were in the age group of 5-13 years, and were studying in mainstream schools. The families resided in New Delhi, the capital of India. They were from the middle socio-economic status and followed Hinduism. The mothers described a wide range of difficulties ranging from financial, emotional to interpersonal in raising their children. However, 21 mothers among them stood out from the rest. Their narratives were optimistic and had positive perceptions. They gave positive meanings to their lives and to the children's situation despite challenges and even though the larger system viewed them negatively. The paper highlights themes that emerged as part of the journey of mothers in developing a more optimistic view of their children's situation and their own self as a person. The research has implications for family interventions.